Construção e Desconstrução da Relação entre Migrações Forçadas e Desafios de Segurança em África - Raquel Freitas (Cadernos de Estudos Africanos)
The debate on transnational challenges to security is framed within the context of the blurring of the traditional concept of state, centred on a territory delimited by borders and with a monopoly of legitimate physical violence. In the African context the debate is guided by two important dimensions: political will and the capacity of the state to protect its citizens. This article suggests that at least the political will dimension is largely constrained by the interpretation of the state on issues of citizenship, in a context where ethnicity is a structuring element of relations and belongings much more powerful than that of citizenship and encompasses the transnational dimension of such relations. Therefore, it is argued that forced migrations should be framed within a societal context, focusing on the role of local populations and local contexts of violence and peace as well as the regional dynamics of integration or rejection of those who flee. In this process it is important to understand the way in which forced migrations are framed as a cause or consequence of insecurity.